Pendampingan Pelaporan Pajak Badan - Leny Suzan; Dewa Putra Krishna Mahardika; Koenta Adji (CV. Multi Kreasi Media, 2024)
Business tax reporting for company is a requirement that must be fulfilled every year. For small and micro entrepreneurs who have limited human resources who understand taxation, the obligation to report taxes can be an important issue that can lead to errors in reporting and paying taxes. With this background, the community service team from the Faculty of Economics and Business, Telkom University, carried out community service activities with the theme